THE INTEGRATION PROCESSES AND POLICY OF INTERSTATE COOPERATION IN THE CASPIAN REGION IN THE CONTEXT OF CHANGING THE MODERN INTERNATIONAL ORDER - M. M. Gadzhiev; I. N. Sokolova (Современная наука и инновации)
The article explores the processes of transformation of the Caspian region from the area of post-Soviet collapse into a place for the implementation of strategically beneficial economic projects. Using the analytical framework of "offensive realism" theory, this study shows that the balance of large and small potentials creates positive opportunities for the implementation of promising economic and infrastructure projects. The author proves that at present the Caspian region demonstrates to the whole world the practical application of the principles of multi-vector and multi-polarity. At the same time, the diplomatic services of the Caspian five have to act precisely in the conditions of a multi-vector foreign policy, which has specific features that correspond to the changing nature of the modern international situation.